Development and Characterization of Grain Husks Derived Lignocellulose Filler Containing Polypropylene Composites. Issue 12 (31st October 2019) - Merijs‐Meri, Remo; Zicans, Janis; Ivanova, Tatjana; Bochkov, Ivan; Varkale, Madara; Franciszczak, Piotr; Bledzki, Andrzej K.; Danilovas, Paulius Pavelas; Gravitis, Janis; Rubenis, Kristaps; Stepanova, Valentina; Locs, Janis
Abstract : Oat and spelt husks (OH and SH, respectively) lignocellulosic biomass derived fillers have been compared with commercial wood flour (WF) in respects to their morphology, chemical composition, bulk density, aspect ratio, and thermal stability. OH and SH have been obtained by both mechanical milling and steam explosion auto‐hydrolysis treatment at various processing conditions. Reinforcement efficiency of OH and SH derived lignocellulosic biomass fillers on the flexural properties of maleic acid‐grafted polypropylene (PPgMA) compatibilized polypropylene (PP) composites is compared with that of WF. The compatibilized PP composites have been manufactured by melt compounding. Flexural test specimens of the compatibilized PP composites have been manufactured by injection molding. It has been demonstrated that both the husks derived lignocellulose fillers can be used to improve flexural modulus and maximal flexural strength of PP, although its modifying effect is somewhat smaller in comparison to WF reinforcement, most probably due to higher cellulose content of the latter. Husks derived lignocellulose filler‐reinforced PP composites, however, demonstrate increased flexibility in comparison to WF‐filled systems. POLYM. ENG. SCI., 59:2467–2473, 2019. © 2019 Society of Plastics Engineers